Study On Colour Coordinates And Maillard Precursors Of Re-Fabricated Rice (Applied Biological Research, 2014)
The effect of feed moisture, screw speed and barrel temperature on colour  coordinates of re-fabricated rice grains were investigated in a co-rotating  twin-screw extruder using response surface methodology. The rice flour obtained from broken rice (< 1/8th- was used in the study. The screw speed was set at five levels between 49  and 150 rpm, barrel temperature between 59 and 110oC and feed moisture  between 31 and 45%. All colour coordinates of re-fabricated grains  evaluated - (total colour difference) and hue angle were significantly affected by the  three process variables. Barrel temperature was the most significant  variable with quadratic effect on a* . Response surface regression  models were established to correlate the colour coordinates of re fabricated rice grains to the process variables. The optimized extrusion  conditions for preparation of re-fabricated grains were 38%, moisture  content, 130 rpm screw speed and 89°C barrel temperature. A significant  change was observed in maillard precursors i.e. sucrose, glucose, fructose  and maltose levels of re-fabricated rice obtained at optimum extrusion
Keywords: Barrel temperature; colour coordinates; extrusion; re fabricated rice; response surface methodology; screw speed